Effect of soil and water conservation on rehabilitation of degraded lands and crop productivity in Maego watershed, North Ethiopia - Gebremariam Yaebiyo Dimtsu; Mulubrehan Kifle; Girmay Darcha (Journal of Degraded and Mining Lands Management, 2018)
Many soil and water conservation (SWC) measures were undertaken to decrease land degradation in Ethiopia. However, evaluation of their performance is essential to understand their success or failure and readjusting accordingly in the future planning.  Therefore, the objective of this study was to evaluate effectiveness of SWC measures in rehabilitation of degraded watershed and increase crop productivity in Maego watershed, Ethiopia. Seventy six sample plots were randomly taken from treated and untreated sub-watersheds for woody species and soil sampling. Crops yield was measured on top side, middle zone and below side of SWC structures. There were significantly higher woody species density and diversity, total nitrogen (TN), soil organic matter (SOM) and soil moisture in the treated uncultivated land than the untreated one. The highest tree and sapling species density and diversity, TN and SOM were recorded on the exclosure part of the treated sub-watershed. Landscape position affected soil fertility, but has no effect on woody species density and diversity. The highest barley and wheat yield was measured on top side of SWC structures. Therefore, physical SWC structures should be integrated with exclosure to enhance rehabilitation of degraded watersheds/landscapes. Integration of biological SWC measures that improve soil fertility are essential on the cultivated land of the watershed. Most of the existing SWC structures, especially the old ones are filled with accumulated sediment, so maintenance is needed.